(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
The teaching of a foreign language in Colombia was regulated by the General Education Law of 1994, since then the government has implemented different strategies, decrees, public policies, and documents that aim to serve as regulations and guidelines for teaching and learning processes focused on the development of communicative competence in English as a foreign language. This article aims to make a review and analysis of the basic standards of English competencies, the basic rights of English learning, the national bilingualism plan, the law 1651 of 2013 and 4 research articles related to the subject, in the cities: Bogota, Medellin and Cali. With the objective of verifying how these policies and decrees are reflected in the institutions and if they are in accordance with the educational reality and the needs of the students. It is evident that although there is interest in the area and it is reflected in the efforts of the government and the different educational actors, there are still shortcomings that we must focus on to make this type of project a reality.